2000
DOI: 10.1063/1.126860
|View full text |Cite
|
Sign up to set email alerts
|

Silicon monolithic microchannel-cooled laser diode array

Abstract: A monolithic microchannel-cooled laser diode array is demonstrated that allows multiple diode-bar mounting with negligible thermal cross talk. The heat sink comprises two main components: a wet-etched Si layer that is anodically bonded to a machined glass block. The continuous wave (cw) thermal resistance of the 10 bar diode array is 0.032 °C/W, which matches the performance of discrete microchannel-cooled arrays. Up to 1.5 kW/cm2 is achieved cw at an emission wavelength of ∼808 nm. Collimation of a diode arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Transverse channels were electroplated on the bottom surface of the heat spreader and placed between each two parallel longitudinal V-channels in silicon substrate. The design provides a local high efficient heat transfer mode (Skidmore et al 2000;Xu et al 2005), which decreases the temperature difference along the flow direction and improves heat transfer efficiency of the microchannel heat sink greatly. In addition, it will be more suitable for integrated fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transverse channels were electroplated on the bottom surface of the heat spreader and placed between each two parallel longitudinal V-channels in silicon substrate. The design provides a local high efficient heat transfer mode (Skidmore et al 2000;Xu et al 2005), which decreases the temperature difference along the flow direction and improves heat transfer efficiency of the microchannel heat sink greatly. In addition, it will be more suitable for integrated fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Unger et al (1999) developed a CVD-diamond heat spreader exhibiting a high thermal conductivity to improve lateral spreading of heat from the active regions, and with the microchannel cooling carrier, high heat transfer characteristics were obtained. Skidmore et al (2000) demonstrated a microchannel heat sink comprising a wetetched Si layer that is anodically bonded to a machined glass block. The intersecting channels provide a larger heat transfer area to minimize the stagnant boundary layer of coolant, which increases the heat transfer efficiency significantly.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Following these recommendations one can expect a cooler lifetime ~10-20Khrs. In the discussion that follows, we review a technology based on micro-channels fabricated in Silicon 4,5 . We believe that this technology offers several key advantages over the existing copper MCCP technology, such as corrosion resistance, electrical isolation to the cooling water, minimal water sealing surfaces, manufacturing simplicity and power scalability.…”
Section: Introductionmentioning
confidence: 99%
“…The diode arrays heavily leverage mass production and commercial markets for diodes. With the commercialization of the LLNL diode packaging 3 by Coherent Inc, an entire high brightness array could be procured. The arrays already being used in the laser meet all of the basic requirements (see table 1) except wallplug efficiency (45 % versus 50 %).…”
Section: Amplifier Technologies: Diodes Crystals and Gas-coolingmentioning
confidence: 99%